2004
DOI: 10.1007/s00125-004-1606-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro generation of insulin-producing beta cells from adult exocrine pancreatic cells

Abstract: Aims/hypothesis: Transplantation of insulinproducing beta cells from donors can cure diabetes, but they are available in insufficient quantities. In this study, we investigated the possibility of generating insulinproducing cells from adult rat exocrine cells cultured in the presence of growth factors. Methods: Rat exocrine pancreatic cells were isolated and treated in vitro with epidermal growth factor (EGF) and leukaemia inhibitory factor (LIF). Analysis was performed by immunocytochemistry, DNA measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
228
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(243 citation statements)
references
References 39 publications
5
228
1
9
Order By: Relevance
“…Growth factorinduced Hnf6 gene expression in cultures was markedly reduced in the presence of the inhibitor of STAT-activation Pp-YLKTK-mts (7.5-fold decrease at day 6 (Po0.01; n ¼ 3)) (Figure 1c). In the presence of nicotinamide in the medium, an agent which was shown to delay the loss of exocrine cell markers, 8,11 we found that 10-20% of all cells expressed Hnf6 in the nucleus. Sixty percent of these cells coexpressed CK20 and 45% coexpressed the acinar marker lipase (some Hnf6-positive cells expressed both CK20 and lipase) ( Figure 5).…”
Section: Growth Factor-induced Upregulation Of Hnf6mentioning
confidence: 80%
See 2 more Smart Citations
“…Growth factorinduced Hnf6 gene expression in cultures was markedly reduced in the presence of the inhibitor of STAT-activation Pp-YLKTK-mts (7.5-fold decrease at day 6 (Po0.01; n ¼ 3)) (Figure 1c). In the presence of nicotinamide in the medium, an agent which was shown to delay the loss of exocrine cell markers, 8,11 we found that 10-20% of all cells expressed Hnf6 in the nucleus. Sixty percent of these cells coexpressed CK20 and 45% coexpressed the acinar marker lipase (some Hnf6-positive cells expressed both CK20 and lipase) ( Figure 5).…”
Section: Growth Factor-induced Upregulation Of Hnf6mentioning
confidence: 80%
“…These observations support our hypothesis of a transdifferentiation from exocrine acinar to endocrine beta cells. 11 …”
Section: Growth Factor-induced Upregulation Of Hnf6mentioning
confidence: 99%
See 1 more Smart Citation
“…While partial pancreatectomy in rodents rapidly induces beta cell regeneration, this process was not observed to occur in patients with pancreatic resections involving more than 50% of the initial pancreatic mass [8]. Evidence for beta cell transdifferentiation has been observed both in vitro and in vivo in animal studies [9,10], but it remains controversial as to whether this occurs in humans [11].…”
mentioning
confidence: 99%
“…Although stem cells were isolated from pancreatic ducts, islets and exocrine tissue the b-cell progenitors have not been identified (Baeyens et al 2005;Carlotti et al 2010;Gao et al 2003;Soria et al 2005). Interestingly, b cells mass increases in vivo significantly after injury and during metabolic demand for example pregnancy or obesity.…”
Section: Introductionmentioning
confidence: 99%